JUSTICE AS CONTRADICTION - V. V. Tuzov (Дискурс)
The article examines the essence of justice, which is the contradicting unity of equality and inequality. The cause of this contradiction lies in the biosocial nature of man. The pursuit to equality is the reflection of essence of the social in public and individual consciousness, which is suggested by social equality of community members and by mutual support among them. Social system develops from the biotic environment of prehuman society as a reaction to a rising contradiction between new productive forces and old resource distribution management. Developing already on its own basis, social system moves away from its essence, influenced by dialectical law, expressed by G. V. F. Hegel with Thesis-Antithesis-Synthesis Model. The return to biotic relations being not complete, the initial social essence continues to operate in a limited form. This leads to modern relationships' controversy and there arises the need in justice that balances equality and inequality in relationships. This balance, according to the author, is ensured by the law that binds the quality of modern relations (inequality) and the essence of the social (equality).